Activated protein C stimulates the fibrinolytic activity of cultured endothelial cells and decreases antiactivator activity. - Sakata, Y (1985)
The effects of bovine activated protein C (APC) on the fibrinolytic activity of cultured bovine aortic endothelial cells were investigated. Confluent monolayers were incubated with purified APC under various conditions and changes in total fibrinolytic activity and in the level of plasminogen activator and plasminogen activator inhibitor (antiactivator) were monitored. The addition of APC to the cells in the absence of other blood or plasma components led to a rapid, dose-dependent increase of fibrinolytic activity both in the media and in cellular extracts. For example, 3.4 micrograms of APC per ml resulted in a 15-fold increase of fibrinolytic activity in the medium within 1 hour. The enhanced fibrinolytic activity reflected increases in both the urokinase-related and tissue-type plasminogen activators produced by these cells. Interestingly, treatment of cells with APC also caused a rapid, dose-dependent decrease in antiactivator activity. Diisopropyl fluorophosphate-inactivated APC did not decrease antiactivator or increase plasminogen activator. Although a small but significant direct (i.e., cell-independent) effect of APC on both fibrinolytic activity and antiactivator activity could be demonstrated, the major portion of these changes appeared to be cell-mediated. These observations indicate that the fibrinolytic potential of cultured endothelial cells is increased by APC and that the enzyme active site is essential for this change. Moreover, the results suggest that one of the primary mechanisms for this stimulation of endothelial cell fibrinolytic activity involves an APC-mediated decrease in antiactivator.